Damage visualization based on frequency shift of single-mode ultrasound-guided wavefield - Shahrim, Muhamad Azim; Harmin, Mohammad Yazdi; Romli, Fairuz Izzuddin; Chia, Chen Ciang; Jung-Ryul, Lee (Aeronautical and Astronautical Society of the Republic of China ,Taiwan, 2022)
Aircraft structures are often subjected to many complex loads that even a minor structural damage can disrupt their load-bearing capacities and lead to catastrophic failure. Ultrasonic wavefield inspection has been available for a while and it is a great method for damage detection. However, the challenge lies in the complexity of the algorithm for mode isolation. For this study, the damage visualization is performed based on frequency shift of single-mode ultrasound-guided wavefield. In principle, the spatio-temporal wavefield data is transformed into the wavenumber-temporal domain and filtering is then performed using Boxcar window before mapping the data. First, a filter width for mode isolation of ultrasonic wavefield in a time-cumulated wavenumber plane is determined. Then, generation of frequency map based on ultrasound spectral imaging (USI) for damage identification is investigated. Last but not least, the comparison of accuracy between frequency analysis algorithm and variable time window amplitude mapping (VTWAM) algorithm is performed. This technique is evaluated to detect artificial damages of 2 mm and 30 mm diameter in steel plates. Overall, the results show that frequency analysis can detect the damage four times faster and the algorithm uses two-dimensional calculation instead of conventional three-dimensional of VTWAM method.